KEPUTUSAN PEMBELIAN ASURANSI JIWA PADA KONSUMEN RURAL: PENGARUH BAURAN PEMASARAN JASA - Silvana Kardinar Wijayati (LPPM University 17 Agustus 1945 Samarinda, 2019)
Indonesia is one of the most promising markets for the growth of life insurance business in Southeast Asia. Low penetration rate and huge population that is scattered in many islands emerge as opportunity and challenge for any company that is willing to operate its insurance business in this country. This study aims to examine the effects of services marketing mix namely product, price, place, promotion, people, process and physical evidence on life insurance purchase decision of rural customers in Kutai Kartanegara Regency, East Kalimantan Province. Data collected through self-administered survey to 76 life insurance policyholders in 3 sub-districts in Kutai Kartanegara Regency such as Tenggarong, Kota Bangun and Sebulu that represented cluster-rural area of East Kalimantan. Multiple linear regression model was used to analyze the data and the results revealed that product, price, people, and physical evidence positively and significantly affect life insurance purchase decision, while place shown negative and significant effect. On the other hand, we found that promotion and process do not significantly affect purchase decision on life insurance.